2002
DOI: 10.1007/bf02867937
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers for early diagnosis of non-‘Q’ wave and ‘Q’ wave myocardial infarction

Abstract: The present study conducted on twenty-five uncomplicated cases of acute myocardial infarction diagnosed by clinical and electrocardiographic findings indicated significantly increased level of cardiac Troponin-T and increased activities of the enzymes total creatine kinase, creatine kinase-MB, aspartate transaminase and lactate dehydrogenase as compared to the twenty-five healthy control subjects. The level of cardiac Troponin-T and the activities of the enzymes total creatine kinase, creatine kinase-MB, aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It is not measured as a single diagnostic indicator, but in conjunction with the troponins or MYO (Mythili et al, 2015). Although, previously, the total CK was used to assess myocardial infarction, Mythili et al, (2015) and Singh et al, (2002) concluded that a CK-MB activity can be sufficient for the early diagnosis of acute myocardial infarction (AMI) (Mythili et al, 2015;Singh et al, 2002). Eriksson et al, (2019) stated that NT-proBNP has a prognostic value in patients with heart failure (Eriksson et al, 2019).…”
Section: Cardiac Markersmentioning
confidence: 99%
“…It is not measured as a single diagnostic indicator, but in conjunction with the troponins or MYO (Mythili et al, 2015). Although, previously, the total CK was used to assess myocardial infarction, Mythili et al, (2015) and Singh et al, (2002) concluded that a CK-MB activity can be sufficient for the early diagnosis of acute myocardial infarction (AMI) (Mythili et al, 2015;Singh et al, 2002). Eriksson et al, (2019) stated that NT-proBNP has a prognostic value in patients with heart failure (Eriksson et al, 2019).…”
Section: Cardiac Markersmentioning
confidence: 99%
“…Treatment with thrombolytic agent can limit the size of infarct. Initial identification and confirmation of AMI are required to make a quick and precise decision, hence, allowing best treatment for the patients with AMI [3,4].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Clinical history and ECG results can diagnose AMI accurately for most AMI patients. However, fews conditions show negative results including the prolonged myocardial injury, age of infarction, location of infarction (high lateral and posterior part of the heart are unable to be detected by ECG), the presence of conduction defects, previous infarction, acute pericarditis or changes in electrolyte concentration [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Acute myocardial infarction (AMI) continues to be a major cause of morbidity and mortality worldwide. 3,4 It remains a leading cause of death in India and represents an enormous cost to health care system. 5 The mortality rate of MI is approximately 30% and for every 1 in 25 patients who survive the initial hospitalization, dies in the first year after AMI.…”
Section: Introductionmentioning
confidence: 99%